Species differences in liver accumulation and metabolism of nucleotide prodrug sofosbuvir. Issue 3 (June 2020) - Wang, Ting; Babusis, Darius; Park, Yeojin; Niu, Congrong; Kim, Cynthia; Zhao, Xiaofeng; Lu, Bing; Ma, Bin; Muench, Robert C.; Sperger, Diana; Ray, Adrian S.; Murakami, Eisuke
Abstract: Sofosbuvir (SOF) is a nucleotide prodrug which has been used as a backbone for the clinical treatment of hepatitis C viral infection. Because sofosbuvir undergoes complex first pass metabolism, including metabolic activation to form its pharmacologically active triphosphate (GS-331007-TP) to inhibit the viral RNA polymerase in the liver, it is difficult to project the human dose for clinical evaluation based on preclinical data. Selecting an appropriate animal model for drug exposure in the target tissue is challenging due to differences in absorption, stability, hepatic uptake, and intracellular activation across species. Efficient liver delivery has been established in human liver following administration in a clinical trial of patients receiving sofosbuvir prior to liver transplantation. Using the clinical liver exposure as a benchmark, we assessed and compared the pharmacokinetic profile in mouse, rat, hamster, dog and monkey. Liver accumulation was also assessed in the PXB mouse model in which the liver is mostly populated with human hepatocytes. At human equivalent dose, the hepatic concentrations of GS-331007-TP in dog and PXB mouse were comparable to those observed in the human livers. In these species, high and sustained levels of GS-331007-TP were observed in both primary hepatocytes in vitro and the liver in vivo . Graphical abstract: Image 1